LONG-TERM CARE AND SOCIAL SECURITY IN INDIA - Goel, Roshni (Innovare Journal of Social Sciences, 2022)
Long-term care (LTC) spending has highest growth in various functions through health expenditures and types of services available and is expected to grow with coming years. A significant share is given by government or compulsory insurance schemes for LTC. LTC spending is the first policy issue for OECD countries. The paper upholds the analysis made by OECD countries for extending country coverage and improving methodology for the future developments in LTC and health. In addition, the paper will also project the expenditure and scope for LTC in BRIICS (Brazil, Russia, India, Indonesia, China and South Africa) countries. The paper will differentiate between health and LTC expenditure and demographic and non-demographic drivers for each study.